Optimalisasi Asesmen Pembelajaran Bahasa Indonesia melalui Pelatihan Pemanfaatan Teknologi Digital - Ghina’a Jayanthi Putri; M. Nur Mustafa; Mangatur Sinaga; Elmustian; Elvrin Septyanti; Tria Putri Mustika; Zulhafizh; Andiana Perizga; Elvan Yudianda (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
The development of digital technology has brought significant changes to the world of education, including in the learning assessment process. Teachers, as the primary implementers of learning, are required to adapt to these developments to ensure more effective, efficient, and tailored assessments to students' needs. This article discusses community service activities focused on training in the use of digital technology to optimize assessment in Indonesian language learning. This activity was motivated by teachers' limited understanding and skills in utilizing digital technology to support the assessment process. Through systematically designed training, teachers were provided with an understanding of the importance of digital assessment, implementation strategies, and its benefits in improving the quality of learning. The results of this activity indicate that this training positively increased teachers' insight and readiness to integrate digital technology into learning assessments. Therefore, the use of digital technology in Indonesian-language learning assessments is a strategic step toward more adaptive, modern, and meaningful learning.